1998
DOI: 10.1039/a807387b
|View full text |Cite
|
Sign up to set email alerts
|

Directly coupled CZE-NMR and CEC-NMR spectroscopy for metabolite analysis: paracetamol metabolites in human urine

Abstract: Direct coupling of NMR spectroscopic detection with both capillary zone electrophoresis (CZE) and capillary electrochromatography (CEC) was applied to the separation of metabolites of the drug paracetamol in an extract of human urine. Continuous-flow CZE-NMR and CEC-NMR allowed the detection of the major metabolites, the glucuronide and sulfate conjugates of the drug and the endogenous material hippurate. Identification of these substances was achieved by examination of individual rows of the NMR chromatogram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 17 publications
0
45
0
1
Order By: Relevance
“…These detection schemes offer unique possibilities because of the additional structural information that can be obtained. On-line coupling of NMR with capillary separation techniques offers many possibilities [193] and was recently coupled to CEC [184, 194±197] as well as being used, for example, in metabolite analysis [195,197] and analgesics [194]. The use of CEC-MS is becoming more popular mainly because of solvent compatibility, in addition to the volumetric flow rates that closely match the requirements of electrospray interfaces available.…”
Section: Detectionmentioning
confidence: 99%
“…These detection schemes offer unique possibilities because of the additional structural information that can be obtained. On-line coupling of NMR with capillary separation techniques offers many possibilities [193] and was recently coupled to CEC [184, 194±197] as well as being used, for example, in metabolite analysis [195,197] and analgesics [194]. The use of CEC-MS is becoming more popular mainly because of solvent compatibility, in addition to the volumetric flow rates that closely match the requirements of electrospray interfaces available.…”
Section: Detectionmentioning
confidence: 99%
“…In particular, the pressure-driven CEC separation was achieved very rapidly, in ¾10 min, with baseline separation of all the compounds used. In other publications by the same group, Pusecker et al 32 and Schewitz et al 33 have shown how CEC-NMR can be used for separation of components in human urine extract, after administration of different drugs. Figure 13 shows individual spectra from paracetemol glucuronide, paracetemol sulfate and hippurate.…”
Section: Nmr Coupled Electrophoretic Separationsmentioning
confidence: 97%
“…A CEC também vem sendo acoplada à espectrometria de massas 68,69 e à ressonância magnética nuclear. 61,70 A detecção espectrofotométrica é realizada através de uma abertura no capilar, denominada janela de detecção, que é obtida removendo-se a poliimida. Esta janela de detecção pode ser feita em uma região do capilar na qual existe fase estacionária; neste caso, a detecção é denominada in-column, ou em uma região vazia do capilar, cuja detecção é denominada on-column.…”
Section: Detecção E Acoplamento Cec-msunclassified